Ultimate load of steel storage systems uprights. (1st September 2018) - Elias, Guilherme Cássio; de Almeida Neiva, Luiz Henrique; Sarmanho, Arlene Maria Cunha; Alves, Vinícius Nicchio; Barbosa e Castro, Ana Flávia
Highlights: 44 experimental tests of steel storage rack perforated uprights. Finite element model used in stability analysis for distortional buckling. Modifications proposed to global buckling curve for perforated members studied. Ultimate loads obtained were less conservative than the obtained with DSM equations. Abstract: This study presents an experimental investigation into the behavior of steel storage rack perforated uprights under axial compression. A total of 44 prototypes comprising eleven cross-sections and four lengths were tested, and a buckling curve of the studied uprights is proposed. The focus of the study is to compare the ultimate loads of the experimental uprights by numerical and theoretical analysis, through modifications to the direct strength method (DSM) equations, using the Brazilian and European design codes. The theoretical values obtained are smaller than the experimental ones, and the interaction of distortional and global buckling is also discussed. The ultimate loads obtained with the proposed buckling curve were less conservative than the DSM equations.